Antimicrobial resistance of Escherichia coli isolated from irrigation waters in selected urban fields around Yamoussoukro lakes in Côte d’Ivoire - Anoman, Tchimonbié Messikely; Kouadio, Aka Niangoran Marie Stéphanie; Doga, Dabé; Ahoudjo, Konan Samuel; Zeze, Adolphe (Journal of Wetlands Ecology, 2020)
This study examined the distribution of Escherichia coli (E. coli) resistant to eleven antibiotics and possible relationships among physico-chemical parameters and these resistances. It was carried out over two years during four climatic seasons in five lakes of the Yamoussoukro lake system in Côte d'Ivoire. The physicochemical parameters of the lakes studied are temperature, pH, dissolved oxygen (DO), dissolved organic carbon (DOC), turbidity, nitrates, orthophosphates and ammoniacal nitrogen. A total of 744 water samples were collected from five (5) lakes belonging to the lake system, over a two-year period, during four dry and four wet seasons. Escherichia coli loadings were evaluated after isolation on specific chromogenic medium COMPASS ECC Agar and the susceptibility to antibiotics by the agar diffusion method. Physico-chemical parameters were evaluated according to international standards. The physico-chemical results showed that the nutrient contents evolved generally from upstream to downstream of the lake system, independently of the sources of pollution of five lakes of system. However, the lake B, in upstream of the lake system, showed levels of nitrate, orthophosphate and ammoniacal nitrogen often similar to the downstream lakes. This demonstrates a source of chemical pollution in this lake, which flows to lakes D and E, which are themselves subject to other pollution. Bacterial loads and bacterial resistance to antibiotics have strictly evolved from upstream to downstream of the system. Most isolates were resistant to ampicillin (16.46%), tetracycline (12.87%), ciprofloxacin (12.86%) and sulfamethoxazole (10.14%). Antibiotic resistance patterns of E. coli isolates were similar in both years studied, but higher during rainy seasons (GRS and SRS). The spearman rank correlations and the principal component analysis (PCA) revealed significant correlations between bacterial resistance to antibiotics in lakes and water physico-chemical parameters. Turbidity and DOC can help to determine the main resistances in the lake D. Orthophosphates can help to understand the resistance of chloramphenicol and the nitrates can help to understand the resistance of ampicillin in the lake B. Resistance in the lakes A, B and C can be influenced by dissolved oxygen. Overall, this study provided baseline information on bacterial resistance in the lakes of Yamoussoukro in Côte d'Ivoire, showing that these lakes could be reservoirs of antibiotic resistance, potentially dangerous to public health.